Rationale and design of the precise percutaneous coronary intervention plan (P3) study: Prospective evaluation of a virtual computed tomography‐based percutaneous intervention planner. Issue 4 (3rd March 2021) - Nagumo, Sakura; Collet, Carlos; Norgaard, Bjarne L; Otake, Hiromasa; Ko, Brian; Koo, Bon‐kwon; Leipsic, Jonathon; Andreini, Daniele; Heggermont, Ward; Jensen, Jesper M; Takahashi, Yu; Ihdayhid, Abdul; et al.
Abstract: Introduction: Fractional flow reserve (FFR) measured after percutaneous coronary intervention (PCI) has been identified as a surrogate marker for vessel related adverse events. FFR can be derived from standard coronary computed tomography angiography (CTA). Moreover, the FFR derived from coronary CTA (FFRCT ) Planner is a tool that simulates PCI providing modeled FFRCT values after stenosis opening. Aim: To validate the accuracy of the FFRCT Planner in predicting FFR after PCI with invasive FFR as a reference standard. Methods: Prospective, international and multicenter study of patients with chronic coronary syndromes undergoing PCI. Patients will undergo coronary CTA with FFRCT prior to PCI. Combined morphological and functional evaluations with motorized FFR hyperemic pullbacks, and optical coherence tomography (OCT) will be performed before and after PCI. The FFRCT Planner will be applied by an independent core laboratory blinded to invasive data, replicating the invasive procedure. The primary objective is to assess the agreement between the predicted FFRCT post‐PCI derived from the Planner and invasive FFR. A total of 127 patients will be included in the study. Results: Patient enrollment started in February 2019. Until December 2020, 100 patients have been included. Mean age was 64.1 ± 9.03, 76% were males and 24% diabetics. The target vessels for PCI were LAD 83%, LCX 6%, and RCA 11%. The final results are expected in 2021. Conclusion: This study will determine the accuracy and precision of the FFRCT Planner to predict post‐PCI FFR in patients with chronic coronary syndromes undergoing percutaneous revascularization.